Clinical Characteristics and Perioperative Complication Profiles of COVID-19–Positive Patients Undergoing Hip Fracture Surgery. (15th October 2021) - Galivanche, Anoop R.; Mercier, Michael R.; Schneble, Christopher A.; Brand, Jordan; Pathak, Neil; Varthi, Arya G.; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Introduction: The coronavirus 2019 (COVID-19) pandemic disease has imposed an unprecedented degree of stress on healthcare systems. This study aimed to understand whether COVID-19 positivity is associated with an increased risk of adverse outcomes after geriatric hip fracture surgery. Methods: From a national administrative claims data set, patients who underwent hip fracture surgery from April 1, 2020, to December 1, 2020 were selected for analysis. COVID-19–positive status was assessed by the emergency International Classification of Diagnoses, 10th Revision, COVID-19 code within 2 weeks before the surgery. Demographic, comorbidity, and 30-day postoperative adverse event information were extracted. Logistic regression before and after 10:1 propensity matching was performed to identify patient risk factors associated with the occurrence of postoperative adverse events. Results: Of 42, 002 patients who underwent hip fracture surgery, 678 (1.61%) were identified to be positive for COVID-19 infection. No significant differences in age, sex, and procedure type were found between COVID-19–positive and COVID-19–negative groups, but the COVID-19–positive patients demonstrated a higher incidence of several comorbidities. These differences were no longer significant after matching. After matching, the COVID-19–positive group had a higher incidence of any, serious, and minor adverse events ( P < 0.001 for all). Controlling for preoperative variables, COVID-19 positivity was associated with an increased risk of experiencing any adverse events (odds ratio [OR] = 1.62, 95% confidence interval [95% CI] = [1.37 to 1.92], P < 0.001), serious adverse events (OR = 1.66, 95% CI = [1.31 to 2.07], P < 0.001), and minor adverse events (OR = 1.59, 95% CI = [1.34 to 1.89], P < 0.001). Discussion: After matching and controlling for confounding variables, COVID-19–positive hip fracture patients had increased odds of multiple postoperative events. Clinicians caring for this vulnerable geriatric population should be mindful of this risk to improve the care for these patients during the ongoing global pandemic.